1979
DOI: 10.1071/ch9791993
|View full text |Cite
|
Sign up to set email alerts
|

Complexes of Carbohydrates with Metal Cations. XI. Paper Electrophoresis of Polyols in Solutions of Calcium Ions

Abstract: Paper electrophoresis in an electrolyte containing calcium ions is a method suitable for the separation and characterization of many polyhydroxy compounds. The method is based on the formation ofcomplexes between the cation and at least two hydroxyl groups of the compounds. Electrophoretic mobilities are listed for many sugars, methyl glycosides and cyclitols. The mobilities convey someinformation on the structure of the compounds. The correlation of electrophoretic mobilities with the configuration and confor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1

Year Published

1983
1983
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 0 publications
1
11
1
Order By: Relevance
“…The formation of such complexes has been studied by a variety of methods, such as determination of changes in solubility, vapor pressure or optical rotation [4], paper electrophoresis [5,6], nuclear magnetic resonance [5], and ultrasonic relaxation [3]. These studies have provided structural and thermodynamic information about the processes between carbohydrates and Ca(II) and also between carbohydrates and Pr(III), an isosteric model of Ca(II) [2].…”
Section: Mechanism and Implications Of Complexationmentioning
confidence: 99%
“…The formation of such complexes has been studied by a variety of methods, such as determination of changes in solubility, vapor pressure or optical rotation [4], paper electrophoresis [5,6], nuclear magnetic resonance [5], and ultrasonic relaxation [3]. These studies have provided structural and thermodynamic information about the processes between carbohydrates and Ca(II) and also between carbohydrates and Pr(III), an isosteric model of Ca(II) [2].…”
Section: Mechanism and Implications Of Complexationmentioning
confidence: 99%
“…TLC was carried out on ion-exchange plates (Polygram Ionex-25 SA, from Macherey-Nagel GmbH, 5160 Diiren, Germany) at ambient temperature (8), HPLC on a Sugar PAK 1 column (Waters) at 93'C. NMR spectra were recorded with a Bruker AM-500 spectrometer.…”
Section: Methodsmentioning
confidence: 99%
“…It seemed desirable to ascertain whether chromatography on cation-exchange resins in the calcium form (7) would be suitable for their separation. In principle, this method does not seem to offer much promise because fructosides do not form strong complexes with cations (8): fructofuranosides do not complex, a-fructopyranosides form only very weak complexes at 0-4-0-5, and p-fructopyranosides weak ones at 0-4-0-5 and 0-2-0-3. However, complexing involving hydroxyl groups of both fructose moie- ties may be favourable (9); in fact, it was found that one isomer, retention times of these anhydfides on a "Sugar PAK di-P-~-fructopyranose 2' .1:2,11-dianhydride (I), complexes (Waters) HPLC column (an ion-exchange column in the ca2+ quite strongly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…sorbitol (Herndon et al 1958). The increased absorption may be associated with the known complex formation between polyhydroxy ligands and a metal cation (Angyal 8z Davies, 1971 ;Angyal et al 1974;Kieboom et al 1975;Angyal & Mills, 1979). Since experimental animals and humans tolerate xylitol better than sorbitol (Makinen, 1978), and since there has been no report on the effects of pentitol feeding on tissue Fe levels, we were prompted to study the effect of peroral xylitol on the tissue Fe levels in the rat.…”
mentioning
confidence: 99%